PEMBERHENTIAN KEPALA DAERAH DALAM KETATANEGARAAN INDONESIA PERSPEKTIF SIYASAH DUSTURIYAH : Telaah Siyasah Syar’iyyah - Suciati, Nur Afifa; Mustafa, Adriana (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
The purpose of this study is to describe the causes of dismissal of regional heads in the Indonesian state administration. Knowing the mechanism of dismissal of regional heads in the Indonesian state administration. Knowing the dismissal of the regional head of the siyasa dusturiyah perspective. The study used qualitative methods with data sources in the form of primary data and secondary data. The results of this study are the causes of dismissal of regional heads in the Indonesian state administration are regulated in article 78 paragraph (2) that regional heads are dismissed for violating laws and regulations, for example committing disgraceful acts such as gambling, drunkenness, and adultery; does not carry out obligations; commit criminal acts such as corruption, collusion and nepotism; commit a crime that threatens the integrity of the country. The mechanism for dismissing regional heads is regulated in Law Number 23 of 2014 concerning Regional Government that if the Governor is dismissed, the DPRD will propose through the Minister to the President with the result of a decision from the Supreme Court. through the Governor as the central government to the Minister with the decision of the Supreme Court. Dismissal of regional heads in Islam has not been explained in detail the procedure for dismissal and in the Qur’an and hadith there is nothing to explain. However, according to Islamic thinkers, a leader can be dismissed if he violates the Shari’a, commits deviations, has organ defects, is completely insane, and loses his freedom.